Analisis Miskonsepsi Siswa SD pada Topik Gerak - Sudarto, Sudarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is a systematic literature review (SLR) adapted from the PRISMA method to identify and analyze the types and prevalence of misconceptions among elementary school students on motion topics. The main goal is to present a comprehensive profile of misconceptions from national empirical studies to support science education interventions at the elementary level. Article subjects include 20 primary studies from SINTA 1-6 journals and other sources (2020-2026), involving 729 elementary school/MI students in 4th - 6th grades from various Indonesian regions. Data collection used systematic searches in Sinta, Garuda, and Google Scholar databases with specific keywords (